2021
DOI: 10.3389/fphar.2021.642400
|View full text |Cite
|
Sign up to set email alerts
|

Ramulus Mori (Sangzhi) Alkaloids (SZ-A) Ameliorate Glucose Metabolism Accompanied by the Modulation of Gut Microbiota and Ileal Inflammatory Damage in Type 2 Diabetic KKAy Mice

Abstract: The novel Traditional Chinese Medicine Ramulus Mori (Sangzhi) alkaloid tablets (SZ-A) are approved by The China National Medical Products Administration for the treatment of type 2 diabetes mellitus (T2DM). However, the extensive pharmacological characteristics and the underlying mechanism are unknown. This study investigated the mechanisms by which SZ-A ameliorates glucose metabolism in KKAy mice, an animal model of T2DM. Diabetic KKAy mice were treated intragastrically with SZ-A once daily for 8 weeks, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…As reported in a phase IIIa clinical study, SZ-A can ameliorate hyperglycemia and reduce HbA1c in type 2 diabetic patients ( Qu et al, 2021 ). In addition, in our previous study, we showed that SZ-A maintains the intestinal flora balance and promotes GLP-1 secretion ( Liu et al, 2021 ). Given that β-cell failure is related to the transition from prediabetes to diabetes, improved β-cell function has a major role in preventing type 2 diabetes.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…As reported in a phase IIIa clinical study, SZ-A can ameliorate hyperglycemia and reduce HbA1c in type 2 diabetic patients ( Qu et al, 2021 ). In addition, in our previous study, we showed that SZ-A maintains the intestinal flora balance and promotes GLP-1 secretion ( Liu et al, 2021 ). Given that β-cell failure is related to the transition from prediabetes to diabetes, improved β-cell function has a major role in preventing type 2 diabetes.…”
Section: Discussionmentioning
confidence: 93%
“…The type 2 diabetic KKA y mice have a similar metabolic syndrome phenotype as humans and exhibit hyperglycemia, hyperinsulinemia, hyperlipidemia and obesity. We have reported that SZ-A ameliorates glucose and lipid metabolism in KKA y mice ( Liu et al, 2021 ). In this study, we again identified that non-fasting and fasting blood glucose was reduced significantly with SZ-A treatment ( Figures 1C,D ), which may be ascribed to the increased insulin secretion and sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional Chinese medicine (TCM) has exhibited satisfactory efficacy and safety over thousands of years of application and is one of the main sources of modern drug discovery [29]. Moreover, TCM extracts exhibit multicomponent and multitarget properties and can have significant efficacy in complex diseases [30].…”
Section: Introductionmentioning
confidence: 99%